croFGD: Catharanthus roseus Functional Genomics Database - She, Jiajie; Yan, Hengyu; Yang, Jiaotong; Xu, Wenying; Su, Zhen (Frontiers in Genetics, 2019)
Catharanthus roseus is a medicinal plant, which can produce monoterpene indole alkaloid (MIA) metabolites with biological activity and is rich in vinblastine and vincristine. With release of the scaffolded genome sequence of C. roseus, it is necessary to annotate gene functions on the whole-genome level. Recently, 53 RNA-seq datasets are available in public with different tissues (flower, root, leaf, seedling and shoot) and different treatments (MeJA, PnWB infection and yeast elicitor). We used in-house data process pipeline with the combination of PCC and MR algorithms to construct a co-expression network exploring multi-dimensional gene expression (global, tissue preferential and treat response) through multi-layered approaches. In the meanwhile, we added miRNA-target pairs, predicted PPI pairs into the network and provided several tools such as gene set enrichment analysis, functional module enrichment analysis and motif analysis for functional prediction of the co-expression genes. Finally, we have constructed online croFGD database (http://bioinformatics.cau.edu.cn/croFGD/). We hope croFGD can help the communities study the C. roseus functional genomics and make novel discoveries about key genes involved in some important biological processes.